2005
DOI: 10.1152/ajpcell.00360.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origins of eukaryotic sodium/proton exchangers

Abstract: Brett, Christopher L., Mark Donowitz, and Rajini Rao. Evolutionary origins of eukaryotic sodium/proton exchangers. Am J Physiol Cell Physiol 288: C223-C239, 2005; doi:10.1152/ajpcell.00360.2004.-More than 200 genes annotated as Na ϩ /H ϩ hydrogen exchangers (NHEs) currently reside in bioinformation databases such as GenBank and Pfam. We performed detailed phylogenetic analyses of these NHEs in an effort to better understand their specific functions and physiological roles. This analysis initially required exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
558
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(579 citation statements)
references
References 173 publications
13
558
2
6
Order By: Relevance
“…The CPA superfamily can be divided in three families (CPA1, CPA2, and NaT-DC-Na + -transporting carboxylic acid decarboxylase -) on the basis of their distinct phylogenetic origin 4,5 . Members of this family have between 333 and 900 amino acid residues and exhibit 10 -14 putative transmembrane segments (TMSs).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The CPA superfamily can be divided in three families (CPA1, CPA2, and NaT-DC-Na + -transporting carboxylic acid decarboxylase -) on the basis of their distinct phylogenetic origin 4,5 . Members of this family have between 333 and 900 amino acid residues and exhibit 10 -14 putative transmembrane segments (TMSs).…”
Section: Introductionmentioning
confidence: 99%
“…No eukaryotic member of the CPA2 family, has been characterized 4,6 . On the other hand, many eukaryotic CPA1 members have been identified and characterized, including many Na + /H + exchangers from fungi, plants, and mammals, The Sodium-Proton Exchangers (NHEs), antiporters of the CPA1 family, catalyze Na + and H + antiport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results indicated that the C-terminally truncated NuoL subunit from E. coli complex I exhibited higher sensitivity towards EIPA than the endogenous Na + transporter(s) present in the intracellular vesicles from S. cerevisiae. Na + uptake observed with control vesicles in the absence of ProtA-NuoL N was probably catalyzed by an intracellular Na + /H + exchanger (NHE) like Nhx1 (Brett et al 2005). Under our experimental conditions, EIPA speciWcally inhibited ProtA-NuoL N but not the other Na + transporter(s) present in the ER vesicles, suggesting that amilorides will be useful tools to probe cation transport by complex I subunits in native S. cerevisiae membranes.…”
Section: (Open Circles and Closed Triangles) Or To Dissipate At Exmentioning
confidence: 59%